MAKING BUSINESS POLICIES AND STRATEGIES IN THE VUCA ERA WITH TECHNOLOGY DEVELOPMENT: A LITERATURE REVIEW - Setyanto Putro; Rianto Rianto; Bima Haria Wibisana (International Journal of Innovative Technologies in Social Science, 2022)
Introduction. Entering the VUCA era, which stands for Volatility, Uncertainty, Complexity, and Ambiguity, is a business situation that leads to uncertainty and is volatile, causing anxiety among business leaders. Creating a business opportunity in the VUCA era requires a strategy owned by many individuals and companies. Being able to run a business in the short term in the VUCA era is not enough, every company certainly wants the business processes they run to be sustainable. So far, the pattern of business thinking is still dominated by short-term thinking. Companies need to innovate to ensure the sustainability of their business processes. Objective. To review the VUCA era and what strategies companies should do to face the VUCA era. Method. The method used is literature research using Elsevier, Science Direct, or other databases to identify the essential attribute of materials. There are 29 pieces of literature found in the database related to the topic. Result and Conclusion. To overcome VUCA era, it is necessary to apply some strategies like vision, understanding, clarity, and agility. If this solution applied, the company can produce innovations or breakthroughs that are getting better, it will also have a good impact on the company’s future sustainability.